2012
DOI: 10.1111/j.1365-2648.2012.06042.x
|View full text |Cite
|
Sign up to set email alerts
|

Student midwives’ views on maternity care just before their graduation

Abstract: In spite of the medicalized context, midwifery education succeeded in educating midwives who hold a woman-centred ideology. Midwifery students linked style of care to a person rather than to a profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…However, others argue that focus groups may permit a detailed examination and interpretation of events by allowing participants to share their experiences and engage in a joint sense making endeavour with the focus group facilitator and other participants [41,42]. The use of focus groups in phenomenology is additionally common in nursing and health studies and is generally justified on the premise that participants who share certain features, can relate to each others comments and share experiences to come to a deeper understanding of the phenomenon [43-45]. We would argue that the use of the focus group, as in this study, added to the data in a similar way, and enhanced rather that inhibited the women’s exploration of their experiences.…”
Section: Methodsmentioning
confidence: 99%
“…However, others argue that focus groups may permit a detailed examination and interpretation of events by allowing participants to share their experiences and engage in a joint sense making endeavour with the focus group facilitator and other participants [41,42]. The use of focus groups in phenomenology is additionally common in nursing and health studies and is generally justified on the premise that participants who share certain features, can relate to each others comments and share experiences to come to a deeper understanding of the phenomenon [43-45]. We would argue that the use of the focus group, as in this study, added to the data in a similar way, and enhanced rather that inhibited the women’s exploration of their experiences.…”
Section: Methodsmentioning
confidence: 99%
“…[59,60,61] In the cultural competence models as well as in healthcare services, the culture of ethnic minority patients is mostly interpreted as an individual deficit that needs to be taken care of by caregivers. [50,63,64] Our results, on the contrary, showed that a shift is needed towards the understanding of culture as being part of the relational care process and thus as emerging from within the interaction between caregivers and patients instead of seeing it as an entity that stands outside these interactions. Here, the findings add more insight into the importance of a shifting perspective on 'culture' from being an 'individual culture-in-isolation' towards a notion of culture as being inter-relational and emerging from within the various care interactions with caregivers.…”
Section: Women Care and Culturementioning
confidence: 58%
“…It is, therefore, difficult for the students to understand and learn the concept in the clinical area – what it means, involves and how it is shaped in practice. As a result, students do not gain sufficient learning experiences and are limited in becoming competent and confident woman-centred practitioners (Rawnson et al, 2009; Van Kelst et al, 2013). In woman-centred care, the woman’s health needs and context are defined by the woman herself (ICM, 2011; RCM, 2014; Sword et al, 2012).…”
Section: Woman-centred Carementioning
confidence: 99%
“…This may provide students with a somewhat limited insight into the value and importance of woman-centred care and women’s overall experiences of maternity care (Lewis et al, 2008). In addition, the lack of women’s lived experiences of the childbirth process and care provision, in theoretical as well as in practical midwifery education, hampers students’ woman-centred care learning experiences (Leap, 2009; Rawnson et al, 2009; Taylor and Hutchings, 2012; Van Kelst et al, 2013). Establishing a culture of acceptance and advocacy for woman-centred care nurtures philosophies that promote the use of woman-centred care.…”
Section: Midwifery Educationmentioning
confidence: 99%